전산화된 임상 데이터에 기반한 환자 분류 체계 및 간호 인력 관리 방안 : 일개 종합병원 분석 사례 - 김경옥; 박경순; 서창진; Kim, Kyoungok; Park, Kyungsoon; Suh, Changjin (한국콘텐츠학회 논문지, 13(3), 2013)
To develop a technique classifying patients based on computerized clinical data followed by validity verification by comparing with nurse's examination. Class scores were determined by nurses for a day on 348 resident patients in 7 wards of a general hospital according to KPCS-1. The class scores were simultaneously evaluated by reviewing the computerized clinical data acquired from the hospital management information system. These two class scores were both significantly different among different departments as well as disease patterns. Intraclass correlation analysis resulted a very high correlation coefficient of 0.96(p<0.01) between the two scoring methods, but the clinical data scores were somewhat higher. An automated patient classification system seemed possible to be developed in future with further enhancement of the present results based on computerized clinical data without manual scoring, which can be applied for performance evaluation as well as workforce planning. 본 연구는 전산화된 임상 데이터를 이용하여 환자 중증도를 분별하는 기법을 고안하고 간호사가 작성한 분류 점수와 비교 분석하여 타당성을 검증하기 위하여 일개 종합병원의 7개 병동 재원환자 348명에게 하루동안 간호사가 수행한 행위를 근거로 환자분류(KPCS-1: Korean patient classification system for nurses) 점수를 간호사가 작성하고, 병원정보시스템에 저장되어 있는 임상 데이터를 이용하여 산정, 수집한 점수와 비교하였다. 간호사가 작성한 점수와 임상 데이터를 이용한 환자 중증도 점수 모두 진료과 및 환자유형에 따라 점수 분포를 비교한 결과 유의한 차이가 있는 것으로 나타나 환자분류의 타당성이 동일하게 검증되었으며, 두 방법 간 에는 상관계수 0.96(p<.001)의 높은 상관성이 있었다. 임상 데이터 기법이 다소 높은 점수를 보였으나 일부 영역의 보완을 거친다면 간호사가 환자분류를 작성하지 않고, 병원정보시스템에 저장된 임상 데이터에 연동하여 자동으로 환자 중증도를 분별하는 시스템 개발이 가능하고 이를 간호인력의 성과관리 및 수급계획 등에 활용 할 수 있을 것으로 기대된다.